2022
DOI: 10.1177/20420188221122486
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and associated predictors for Bethesda III–VI for reporting thyroid cytopathology in Royal Commission Hospital, Kingdom of Saudi Arabia

Abstract: Background: Thyroid cancer is increasing globally and is currently the most prevalent endocrine malignancy. Recent data show an increase in the incidence of thyroid cancer in the Kingdom of Saudi Arabia (KSA). Thyroid ultrasound and fine-needle aspiration cytology (FNAC) are the cornerstones in managing thyroid nodules. We conducted this study to evaluate the prevalence and the associated predictors for thyroid nodule Bethesda III–VI in eastern KSA. Methods: A retrospective study was conducted between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…This may be explained by the influence of Dio2, the enzyme responsible for the conversion of T4 to T3 [ 40 ], which is associated with an increased risk of increased insulin resistance and T2DM [ 39 ]. The results of the present study are in accordance with the outcomes of many studies that have shown no significant associations between DM and other associated predictors (gender, FT4, TSH, thyroid status, hematological indices, vitamin D levels and the ACR TI-RADS scoring system) [ 38 , 58 - 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…This may be explained by the influence of Dio2, the enzyme responsible for the conversion of T4 to T3 [ 40 ], which is associated with an increased risk of increased insulin resistance and T2DM [ 39 ]. The results of the present study are in accordance with the outcomes of many studies that have shown no significant associations between DM and other associated predictors (gender, FT4, TSH, thyroid status, hematological indices, vitamin D levels and the ACR TI-RADS scoring system) [ 38 , 58 - 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, the observed prevalence in Saudi Arabia (6.1%), Ethiopia (11.5%), and the United Kingdom (18.3%) surpassed the findings of the current investigation. 3 , 4 This could be due to differences in variances in the definition of malignancy, the selection of study participants, the methods employed for data collection and analysis, and differences in the sample size can contribute to the observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…2 The prevalence of thyroid cancer is increasing globally, and it is the most prevalent endocrine cancer worldwide. 3 About 1-5% of all cancers in women and less than two percent in men worldwide are thyroid cancers. 4 About 5-10% of thyroid lesions are malignant and require surgical and pharmaceutical treatment.…”
Section: Introductionmentioning
confidence: 99%